Sensitive chemiluminescence determination method for 2, 4, 6-trinitrotoluene based on the catalytic activity of amine-capped gold nanoparticles. (1st December 2016) - Hassanzadeh, Javad; Khataee, Alireza; Bagheri, Nafiseh; Lotfi, Roya
Abstract : TNT can efficiently quench the high intensity CL emission of a rhodamine B–KMnO4 –EDA capped AuNP CL system. Abstract : A simple, sensitive and selective chemiluminescence (CL) assay for the determination of 2, 4, 6-trinitrotoluene (TNT) is described due to its high importance in addressing security and environmental problems. The CL system was based on the reaction of rhodamine B (RB)–KMnO4 catalyzed by gold nanoparticles (AuNPs). TNT could efficiently quench the CL emission due to its selective interaction with amine groups embedded on the AuNP surfaces. This quenching effect led to the design of a highly sensitive CL turn-off probe for the detection of TNT. Various key factors including the RB, KMnO4 and AuNP concentrations were optimized. TNT could be quantified in the concentration range of 0.27 to 20 nmol L −1, with a detection limit (3 σ ) of 0.045 nmol L −1 under optimal conditions. Compared to other NP-based techniques, the developed probe has a better detection limit as demonstrated by the successful analysis of environmental samples.